A Miniature Terracotta Figurine from Nikonion - Głuszek, Inga (Acta Archaeologica Lodziensia, 2019)
The terracotta figurine which is the subject of this paper was found during excavations in Nikonion in 2011. The article seeks to analyse the figurine in order to suggest an origin for the prototype of the terracotta representation, considering that it constitutes a relatively schematic depiction, that it might be late Classical in date judging by the archaeological context.